Pengaruh Pengalaman Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan Kantor Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan se Solo Raya - Wahyu Pratiwi, Dinda; Darsono, Darsono (Edupedia Publisher, 2023)
This study aims to examine the effect of work experience, work discipline, and work environment on the work performance of employees of the Healthcare Administration Agency (BPJS) in Solo Raya. This type of research is a quantitative descriptive study using primary data and secondary data. Data collection using a questionnaire method. The population in this study were all BPJS employees in Solo Raya, totaling 70 respondents and the sample collection method used probability sampling; simple rondom sampling. The analysis used is multiple linear regression. The results of this study indicate that there is a simultaneous (jointly) significant effect of work experience, work discipline, and work environment on work performance with an F value of 15, 325 with a sig = 0.000. For BPJS Kesehatan throughout Solo Raya, it can improve the quality of existing human resources. By improving and extending work experience, work discipline and work environment and improving it so as to improve employee performance through the indicators in this study.